‘Like being on death row’: Britain and the end of coal, c. 1970 to the present - Arnold, Jörg (Tatlor & Francis, 2017)
ABSTRACT The introduction draws on the work of Raymond Williams to identify the ‘structures of feeling’ that surround the figure of the coal miner in contemporary British culture. As an analysis of the media coverage of the closure of the UK’s last deep-coal mine in December 2015 demonstrates, mine workers were cast as ‘residual proletarians’ whose modes of being and consciousness were portrayed as both admirable and pitifully out of date. The introduction goes on to demonstrate the dominance that selective memories of the miners’ strike of 1984/1985 exert over contemporary understandings of coal mining. Drawing on the work of Williams again, the introduction reflects on how certain images and tropes have reached hegemonic status while others have been marginalised. The introduction concludes by arguing that historical scholarship must extricate itself from the stranglehold of ‘1984/85’ and contends that the true significance of coal for contemporary British history lies in the extraordinary range of emotions, meanings and significations with which both the industry and the miners were invested by the contemporaries themselves.